Variation in Development of Contrasting Rice Cultivars - Senanayake, N.; Naylor, R. E. L.; De Datta, S.K.; Thomson, W.J. (Cambridge University Press, 1994)
Experiments were conducted in glasshouses at IRRI, Philippines, during 1987 and 1988 to identify varietal differences in apical development using six rice cultivars having extreme characters; Jirasar 280 (early senescence), Neo-Dunghan 1 (late senescence), Macunting (small seeds), ABB (large seeds), C12474–1 (long culm), and B581–A6–458 (short culm); and five cultivars, IR20, IR22, IR34, IR54, IR64, of the same growth duration.The length of time from physiological panicle initiation (PI) to flowering varied from 25 to 50 days. The onset of physiological PI occurred when the fourth penultimate leaf was fully exserted. The visual panicle initiation stage (VPI) coincided with spikelet differentiation in all cultivars. Nitrogen top-dressing at 55–57 days before the anticipated maturity date (the present N management recommendation) did not coincide with the actual panicle initiation stage in any of the cultivars and the major yield determinants (i.e. the primary and secondary branches) therefore differentiated in conditions of internal nitrogen shortage. Spikelet abortion took place both before and after flowering. Reduction of pre-flowering abortion is important in increasing rice grain yields and could be achieved by improved N management. It is important to recognise cultivar differences and periods of loss of potential yield in developing efficient N management protocols.